The Prosthetic Promise: Breast Cancer and Technologies of Corporeal Repair. Issue 1 (2nd January 2018) - Ehlers, Nadine
Abstract: This article explores how the body/materiality might be understood in relation to the tekhnē (the technologies, techniques, and craft) of repair implicit within breast reconstruction technologies. Breast reconstruction technologies promise to repair the body following breast cancer surgery by returning the body to its previous 'normativity' and supposed state of corporeal 'wholeness', both of which rest on the ability to visually signify and embody 'femininity' via the materiality of the breast. Such technologies, however, delimit the possibility of realising the prosthetic promise in two senses. First, they can only achieve this supposed repair through processes of corporeal disaggregation (where parts of the body are removed and others re-arranged). Second, such repair is always contingent . 'Return to' or 'repair of' the body prior is vexed, then, raising the question: what kind of renewal – and materiality – might arise from the precarity of repair?